Ethnicity, maternal risk, and birth weight among Hispanics in Massachusetts, 1987-89. - Cohen, B B (1993)
National data reveal that low birth weight and infant mortality rates among Hispanics are, in general, between the rates for whites and those for blacks. The question remains, do differences in low birth weight reflect distributions of known risk factors, or do ethnic differences persist after simultaneously adjusting for intervening variables? In this study, Massachusetts birth certificate data for 206,973 white non-Hispanic infants and 19,571 Hispanic infants are used to examine differences in low birth weight between white non-Hispanic and Hispanic infants, as well as variation among seven subgroups of Hispanic mothers--Puerto Rican, Dominican, Central American, South American, Mexican, Cuban, and other Hispanic. Regression analysis is used to estimate the association between risk factors and birth weight and the relative risk of low birth weight. Risk factors include ethnicity, demographic characteristics, biological factors, access to prenatal care, and infants' conditions. Results indicate substantial variation in mean birth weight, low birth weight, and levels of risk among Hispanic subgroups and between Hispanics and white non-Hispanics. Puerto Rican infants had the lowest mean birth weight and, in general, the highest level of risk factors in this population. None of the adjusted odds ratios for low birth weight for any Hispanic group was significantly elevated at the 95 percent level compared with white non-Hispanics. Findings in this study confirm the previous observations of the wide variation among Hispanic subgroups and the high level of risk among Puerto Ricans.(ABSTRACT TRUNCATED AT 250 WORDS)